Unveiling the Complexities of Spousal Rights Abuse: An Exploration within the Afghan Socio-Legal Milieu and Islamic Jurisprudence - Aminullah Poya; Habiburrahman Rizapoor (CV. AFDIFAL MAJU BERKAH, 2023)
This study endeavors to conduct a comprehensive investigation into the intricate matter of rights abuse within the context of Islamic jurisprudence, with a specific focus on instances of spousal rights abuse within the cultural and legal framework of Afghanistan. The primary objective of this research is to elucidate the diverse manifestations of abuse, regulatory mechanisms, potential remedies, and the foundational marital norms that contribute to this phenomenon. Employing a methodological approach that combines inductive reasoning and analytical techniques, this inquiry systematically navigates the nuanced dimensions of spousal rights abuse, unraveling its implications while proposing pragmatic measures to alleviate its adverse societal repercussions. Situated within the intricate socio-cultural landscape of Afghanistan, this study delves into the comprehension and practices of prevailing marital norms. Special emphasis is placed on grasping the dynamics of spousal rights abuse, encompassing scientific, economic, ethical, and cultural dimensions. Through meticulous data collection from primary and secondary sources, this research rigorously examines Islamic jurisprudence to illuminate distinct forms of abuse, their regulatory constraints, and defining criteria, culminating in thorough discourse and analysis. The findings of this investigation underscore the extensive implications of spousal rights abuse, underscoring its deleterious effects on individuals, families, and the broader society. Notably, this study identifies a substantial void within the existing literature concerning the application of abuse within the domain of rights exercise within the familial context of Afghanistan. The research advocates for the establishment of a committee comprising jurists and subject experts, dedicated to addressing and rectifying this pervasive issue. With a theoretical and applied approach, this research offers a unique vantage point on the subject of abuse in rights exercise, with particular attention to gender dynamics. By suggesting feasible remedies and accentuating the significance of education and awareness, this study serves as a valuable reservoir of information for individuals, governmental bodies, and stakeholders engaged in the resolution of spousal abuse-related disputes within the Afghan context.